2021
DOI: 10.1021/acsaelm.0c00610
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Crystal Formation and Electrical Variability Reduction in Hafnium-Oxide-Based Ferroelectric Memory by Thermal Engineering

Abstract: In this paper, we achieved excellent variation control, endurance enhancement, and leakage reduction in zirconium (Zr)-doped hafnium oxide (Hf 1−x Zr x O 2 ) based ferroelectric films by the germination of large ferroelectric grains through extending the duration of rapid thermal annealing without increasing the temperature beyond 700 °C. The pivotal point of this work is to reduce electrical variations in ferroelectric capacitors, which we attribute to the random variation in ferroelectric and dielectric phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Nanoscale n-type and p-type tri-gate Fe-finFETs were fabricated on an SOI wafer using a gate first self-aligned high-K and metal gate process (De et al, 2021b). The devices under consideration have a gate length (L) of 70 nm and fin width (W) of 20 nm.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Nanoscale n-type and p-type tri-gate Fe-finFETs were fabricated on an SOI wafer using a gate first self-aligned high-K and metal gate process (De et al, 2021b). The devices under consideration have a gate length (L) of 70 nm and fin width (W) of 20 nm.…”
Section: Methodsmentioning
confidence: 99%
“…The second is parasitic charge clouds at the interface and fin line-edge-roughness (LER), which increases the charge-trapping probability and inhibits fast WRITE. Previous reports have shown that surface treatment can alleviate the issues associated with the poor interface quality and reduce the device-to-device variations up to a maximum 10% deviation from the mean value (De et al, 2021a;De et al, 2021b). The final and third one is systematic retention degradation, which directly impacts the inference operation (Baig et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hafnium oxide HfO 2 is a remarkable material with various applications. Currently, the Hafnium oxide-based material is mainly used as the ideal memory material, [1,2,3,4,5] i.e. ferroelectric Si-doped HfO 2 [6,7,8,9] due to its ferroelectric property.…”
Section: Introductionmentioning
confidence: 99%